PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK ONE TO ONE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 LUBUK SIKAPING TAHUN PELAJARAN 2013/2014 - Mulia Syahri, Siska; Zulfaneti, Zulfaneti; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTThis research is motivated by the students understanding of mathematical concepts are still low and students are not motivated to learn mathematics. This research is head for determine whethert students understanding of mathematical concepts by using cooperative learning one to one techniques model is better than students by conventional learning and to find out how students matematic learn motivation by applying the cooperative learning model one to one techniques. Type of this research is experimental. The population of this research is VIII class students of the SMPN 2 Lubuk Sikaping. Instrument used in this reaserch is questionnaire of motivation and the last test for the understanding of mathematical concepts. The test form used is essay form with reliabilities test is . Data analysis techniques used is t test one side at the α = 0.05. Hypothesis test results obtained that  mean while , because . So the hypothesis of this research is accepted and with the resault can be inferred that students understanding of matematical concept by applying the cooperative learning one to one techniques model is better than student  understanding of matematical concept taught by conventional learning the VIII class students of the SMPN Lubuk Sikaping junior high school in lessons 2013-2014.